Central Retinal Artery Doppler Indices Change in Hypertensive Adults: A Case-Control Study - Khalid Abdulqader, Shaymaa; Najm, Lubna Hasan; Noor,; Nabeeha, (Scripta Medica, 2025)
Background/Aim: Hypertension had significant microvascular complication involving the ocular circulation. Colour Doppler imaging (CDI) using various flow indices can be used to assess the blood flow properties of the central retinal artery (CRA) in hypertensive adults. Aim of study was to evaluate the differences in CRA Doppler indices between normotensive and hypertensive individuals.Methods: This case-control study design was undertaken in the Ultrasound unit at Al-Kindy teaching hospital for 3 months (January 2025 to March 2025), including 60 healthy controls and 60 young hypertensive patients on treatment. For each patient, two sets of data were gathered: demographic data including (age, gender and the body mass index BMI) and measurements of the Doppler indices of the CRA including the pulsatility index (PI), resistive index (RI), flow velocities: peak systolic velocity (PSV), end diastolic velocity (EDV) and arterial diameter (D). Doppler indices were compared and analysed between the cases and controls. Results: Hypertensive patients show a not significantly decreased PSV and EDV in comparison with the control group (p = 0.122 and 0.05, respectively). However significant increases in RI and PI were detected in hypertensive group (p < 0.001 and 0.003, respectively). The hypertensive patients show a significantly decreased luminal diameter of the CRA in comparison to the control group (p < 0.001). For RI, the AUC was 0.837, 95 % confidence interval (CI) = 0.755 - 0.918, p < 0.001. The sensitivity and specificity of RI at cutoff = 0.635 were 88.3 % and 70 %, respectively.Conclusion: There is a significant difference in Doppler indices of the CRA in hypertensive patients compared with the non-hypertensive patients. Among them, RI exhibited the highest diagnostic accuracy.